2015
DOI: 10.7567/jjap.54.08ke10
|View full text |Cite
|
Sign up to set email alerts
|

MBE-grown InGaAsP solar cells with 1.0 eV bandgap on InP(001) substrates for application to multijunction solar cells

Abstract: In this study, we have developed the first ever solid-source molecular beam epitaxy (SS-MBE)-grown In0.81Ga0.19As0.43P0.57/In0.47Ga0.53As dual-junction solar cells grown on InP substrates with a 1.0/0.7 eV bandgap for use in mechanically stacked multijunction solar cells. We studied the adsorption efficiencies of As2 and P2 to determine the optimal parameters for the growth of lattice-matched In0.81Ga0.19As0.43P0.57 by SS-MBE. The adsorption efficiency of As2 was found to be seven times greater than that of P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Since Dimroth et al reported the wafer bonded four-junction GaInP/GaAs//GaInAsP/InGaAs solar cell with a highest efficiency of 46.0% at approximately 500 suns, [5] the InGaAsP solar cell has received more and more attention motivated by achieving higher conversion efficiency. [6][7][8][9][10][11][12] In this regard, a better understanding of the internal behaviors of carriers in InGaAsP solar cell should be desired. On the other hand, as is well known, quaternary alloy with different ionic radii is difficult to grow [13] because the miscibility gap inhibits the mixing of constituents within the alloy, different kinds of clustering (atomic ordering, quantumdots-like formations, and atomic content fluctuation, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Since Dimroth et al reported the wafer bonded four-junction GaInP/GaAs//GaInAsP/InGaAs solar cell with a highest efficiency of 46.0% at approximately 500 suns, [5] the InGaAsP solar cell has received more and more attention motivated by achieving higher conversion efficiency. [6][7][8][9][10][11][12] In this regard, a better understanding of the internal behaviors of carriers in InGaAsP solar cell should be desired. On the other hand, as is well known, quaternary alloy with different ionic radii is difficult to grow [13] because the miscibility gap inhibits the mixing of constituents within the alloy, different kinds of clustering (atomic ordering, quantumdots-like formations, and atomic content fluctuation, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Considering the low growth temperature and phase separation that result in deep centers and=or defect states, the quaternary compound of InGaAsP with a band gap of 1.05 eV is difficult to grow by MBE. 7) Very recently, an InGaAsP SC with an efficiency of 10.5% and an InGaAs= InGaAsP dual-junction SC with an efficiency of 3.7% were reported; 8) such a report indicates a great potential to improve the device performance. An efficient back-surface-field (BSF) layer can confine the photogenerated minority carriers and keep them within reach of the p-n junction and, at the same time, ensure the transport of majority carriers to be efficiently collected.…”
Section: Introductionmentioning
confidence: 99%